Impact of a thermisation treatment on oxytetracycline spiked ovine milk: Fate of the molecule and technological implications. (October 2018) - Cabizza, Roberto; Rubattu, Nicolino; Salis, Severyn; Pes, Massimo; Comunian, Roberta; Paba, Antonio; Daga, Elisabetta; Addis, Margherita; Testa, M. Cecilia; Urgeghe, P. Paolo
Abstract: A few studies have been published on the distribution of oxytetracyline (OTC) residues present in milk among cheese, whey, and milk protein fractions, throughout cheese-making, most of them, focused on the effect of pasteurization and Ultra High Temperature (UHT) treatments, and carried out on cow milk. This study aimed to investigate the impact of a thermisation treatment of ovine milk spiked with oxytetracycline at MRL (maximum residue limit) and half MRL, on the fate of the molecule, and the effect of OTC residues on starter culture development and cheese composition. The antibiotic recovery and partition from milk into whey and cheese were assessed by liquid chromatography-high resolution mass spectrometry (LC-HRMS). Starter and non-starter microflora development was monitored by viable plate counts. Milk thermisation did not affect OTC recovery, partition and cheese chemical composition. On a dry matter basis, an OTC reduction between 15 and 19% was calculated in 60-day cheese, at MRL and half MRL, respectively. OTC caused a dose-dependent difference in the time required to reach pH 5.60, which was significantly higher (P < 0.05) at MRL level compared to half MRL and control, allowing coliform bacteria to reach 6 log CFU g −1 in 1-day MRL OTC cheeses. Highlights: Thermisation did not reduce the oxytetracycline residues in MRL spiked ovine milk. Low levels of oxytetracycline cause a dose-dependent acidification delay in cheese. LC-HRMS method allowed to obtain an overall recovery of the molecule spiked in milk. Most of oxytetracycline is recovered in ovine cheese at the end of cheese-making. Oxytetracycline residues in cheese from spiked milk decreased during ripening.